2010
DOI: 10.1097/opx.0b013e3181fd6188
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Sensitivity as an Ophthalmic Marker of Diabetic Neuropathy

Abstract: NCCE is a sensitive test for the diagnosis of minimal and more advanced diabetic neuropathy and may serve as a useful surrogate marker for diabetic and perhaps other neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Such dysfunction could arise from a peripheral neuropathy involving the afferent sensory nerves from the ocular surface affecting corneal sensitivity and the autonomic (efferent) nerves responsible for innervating the tear-component secreting glands and the lacrimal and meibomian glands [35, 40, 41]. This is supported by the current results of reduced corneal sensitivity; however the previously reported association between corneal sensitivity and peripheral neuropathy failed to reach statistical significance in the current study ( r = 0.24, P = 0.08) [42]. Reduced tear secretion has previously been identified in patients with type 2 diabetes relative to healthy controls [8, 11].…”
Section: Resultssupporting
confidence: 83%
“…Such dysfunction could arise from a peripheral neuropathy involving the afferent sensory nerves from the ocular surface affecting corneal sensitivity and the autonomic (efferent) nerves responsible for innervating the tear-component secreting glands and the lacrimal and meibomian glands [35, 40, 41]. This is supported by the current results of reduced corneal sensitivity; however the previously reported association between corneal sensitivity and peripheral neuropathy failed to reach statistical significance in the current study ( r = 0.24, P = 0.08) [42]. Reduced tear secretion has previously been identified in patients with type 2 diabetes relative to healthy controls [8, 11].…”
Section: Resultssupporting
confidence: 83%
“…It has been demonstrated in both human and animal subjects that diabetes alters the structure of corneal nerves, and this may be an early marker for diabetic PN. 26,12,1825 We propose that a diabetes-induced loss in corneal nerve density will translate into a decrease in cornea sensitivity in response to corneal stimulation through hypertonicity that can be evaluated by capturing and measuring behavioral changes in facial and/or ocular movement. Quantifying these behavioral changes could provide an objective screening tool for detection of PN that can be easily performed during a routine eye examination.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, we developed an objective functional test of corneal sensitivity. 6 The method uses hyperosmolar eye drops to activate transient receptor channel-8 receptors (TRPM8) in the cornea, which results in reflex blinking and squinting if the nerves are intact. 7 As diabetic PN develops, damaged corneal nerves lose sensation, which decreases the reflex response to corneal stimulation.…”
mentioning
confidence: 99%
“…It has been suggested that optometrists can use color vision screening to detect changes in early diabetes and may have a role to play in detecting diabetic neuropathy by measuring corneal sensitivity. 98,99 …”
Section: Patient Evaluationmentioning
confidence: 98%